Storage Limitation Statements: Temperature – Herbicides - Frederick M. Fishel (EDIS)
This 8-page guide provides information about how temperature affects storage of agricultural herbicides. A table is included that lists many common agricultural herbicides registered for use in Florida, with storage limitation statements. Written by Frederick M. Fishel, and published by the UF Department of Agronomy, April 2013.